The American Revolution : History Smashers #5 - Messner, Kate; Meconis, Dylan (New York : Random House, 2021)
"A book that explores the hidden truth about the American Revolution featuring sidebars, illustrations, photos, and graphic panels"--.
War of worlds -- Taxes, turmoil, and tea -- Midnight rides and the shot heard round the world -- Inching toward independence -- The battle over the Declaration -- The spirit of '76 -- Snowstorms, spies, and the element of surprise -- Smallpox, spies, and the Battle of Saratoga -- Now what?
Includes bibliographical references and index.
Ages 8-12
Keywords: United States -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- History -- Revolution, 1775-1783